Comparison of the nutritional value of mysore thorn borer (Anoplophora chinensis) and mealworm larva (Tenebrio molitor): Amino acid, fatty acid, and element profiles. (1st September 2020) - Wu, Ricardo A.; Ding, Qingzhi; Yin, Litao; Chi, Xiuwei; Sun, Nianzhen; He, Ronghai; Luo, Lin; Ma, Haile; Li, Zhikun
Highlights: The nutritional value of mysore thorn borer was determined and compared to mealworm larva and conventional food sources. Mysore thorn borer is a good source of nutritional and functional compounds. The nutritional content of mysore thorn borer is comparable to conventional livestock. This study demonstrates the suitability of mysore thorn borer as alternative food source able to solve nutritional problems. Abstract: There is increasing interest in using insects as an alternative nutrient source and Mysore thorn borer (MTB) ( Anoplophora chinensis ) might have nutritional and functional relevance for humans. The nutritional composition of MTB (amino acids, fatty acids, and elements profiles) was examined and compared with mealworm larva (MWL) ( Tenebrio molitor ). MTB was found to contain 19 amino acids, including all essential amino acids. A total of 16 fatty acids were detected including polyunsaturated fatty acids (e.g. α-linolenic acid and linoleic acid). Moreover, MTB had a low n − 6/n − 3 ratio and contained some essential elements, such as iron, zinc, calcium, and potassium. These results demonstrated that MTB might be a potential source of nutritional compounds for human consumption.